Sandwich Generation: Copy Paste Nilai Teori Agensi dalam Keluarga Akuntan - Dini Fatihatul Hidayah; Krisno Septyan (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to reveal the family dynamics of